Examining the Relationship between Total Factor Productivity and Crime Rate: Evidence from US Courts, 1960-2011 - BENLİ, Hande Emin; BENLİ, Erman (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).05, 2018)
Following the literature, undesirable attitudes affect productivity and growth negatively. Societal attitudes such as criminal and violent behavior are the important and ignored long-run determinants of total factor productivity. This paper aims to examine the relationship between total factor productivity and crime rate in U.S. for the period 1960-2011 by using production function approach. FM-OLS method is employed to analyze this long-run relationship. Productivity equation also analyzes the effect of unemployment rate and inflation rate to total factor productivity. The empirical results indicate that unemployment rate has no meaningful relationship with total factor productivity while inflation rate has a negative impact on this long-run growth indicator. Suitable with the aim and expectations of this study, the main empirical finding is the negative impact of crime rate on total factor productivity.